Significance of Bottom of Pyramid for Corporate India - Guruprasad, M.; Patnaik, Sujit (Indian Journal of Marketing, 2007)
"Sell to the poor if you want to be rich" were the words spoken by the experts in Rural Marketing. Every marketer loves to reach out to the fat wallets where the selling is obvious, easy and conspicuous. But there is a segment arising alongside that doesn’t claim to be glamorous on the outside but has an invisible power and an untapped capacity to spell riches for the targeting marketer if tackled in the right manner - subject to their needs, requirements, aspirations, purchasing power, preferences, culture, social conditioning, etc. This segment began to be noticed by the corporate India in a very serious and potential manner only in the last few years – although there have been isolated examples of company-specific efforts to convert their poverty to balance sheet gains.